Dr Punctal Polyp, First Case Presentation - Qidwai, Nazia (Journal of Rawalpindi Medical College, 2024)
Polyps are exophytic or sessile lesions growing from the mucosal surface. They are usually idiopathic. They may be neoplastic or nonneoplastic. 1 They have been reported to arise in the ear canal, cervix, colorectal area, nose, uterus, stomach, throat, vulva, bronchus and urinary bladder. 4 Punctal polyps have never been reported in the literature before. A thirty-year-old male patient presented to the oculoplastic clinic with the complaint of small polypoidal masses present in the medial corners of both eyes. They had been there for the last 3 months and were associated with itching and foreign body sensations. There was no systemic history of any allergy or use of any anti-allergic drugs. An excisional biopsy of these lesions was done and sent for histopathology. They were found to be polypoidal fragments of tissue covered by stratified squamous epithelium. The stroma was fibrous and showed mild chronic non-specific inflammation composed of lymphocytes and few plasma cells. Few blood vessels were seen. These were labelled as fibroepithelial punctal polyps. This is a rare location of presentation of polyp and hasn’t been reported before. It is important to distinguish it from papilloma and bear the possibility of a polyp in mind to avoid unnecessary medical management.